PERAN HUKUM TATA NEGARA ADAT KALILI “TONDA TALUSI” DALAM PENGUATAN MODERASI BERAGAMA DI LEMBAH PALU - Randy Atma R Massi; Mursyid, Besse Tenriabeng (Qaumiyyah: Jurnal Hukum Tata Negara, 2024)
Palu City is the capital of Central Sulawesi Province. The original inhabitants of Palu City are the Kaili tribe. Most of the population adheres to Islam (86.99%), Christianity (10.65%), Catholicism (0.90%), Hinduism (0.93%), Buddhism (0.50%), and Confucianism (0.001%). The potential for diversity certainly contains both positive and negative values. Conflicts due to ethnic and religious diversity often occur. What is interesting is that the largest tribe in the Palu Valley, which has an open character with differences and diversity, is the character of the Kaili people, so this is interesting to study, especially regarding the abilities of the Kaili tribe with its system called "Tonda." Talusi” can make the City of Palu one of the cities that is able to easily instill the value of religious moderation. This research is qualitative research, a type of library research. The research results show that Tonda Talusi is the philosophy of the Kaili indigenous people, which describes the harmonious relationship between humans and the universe, with fellow humans, and with God. Tonda Talusi means three supports (furnaces) for the lives of the Kaili indigenous people. The principles of togetherness in Tonda Talusi's philosophy include the 3 pillars of life of the Kaili traditional community, which are based on good values, namely: Matuvu Mosipeili means seeing each other, Matuvu Mosiepe means hearing each other, and Matuvu Mosimpotove means loving each other. Abstrak Kota Palu adalah Ibu Kota Provinsi Sulawesi Tengah, penduduk asli Kota Palu adalah Suku Kaili. Sebagian besar penduduknya memeluk Agama Islam (86,99%), Kristen (10,65 %), Katholik (0,90 %), Hindu (0,93 %), Budha (0,50 %) dan Kong Hu Cu (0,001 %). Potensi keragaman tersebut tentu memuat nilai positif maupun negatif. Konflik akibat faktor keragaman suku dan agama kerap terjadi, hal yang menarik, ketika suku terbesar di lembah Palu yang mempunyai karakter terbuka dengan perbedaan dan keragaman merupakan karakter masyarakat Kaili sehingga hal ini menarik untuk digkaji terutama terkait kemampuan suku Kaili dengan sistemnya yang disebut dengan “Tonda Talusi” dapat menjadikan Kota Palu menjadi salah satu kota yang mampu dengan mudah menanamkan nilai moderasi beragama. Penelitian ini merupakan penelitian kualitatif, jenis penelitian library research. Hasil penelitian menujukan bahwa Tonda Talusi adalah filosofi masyarakat adat Kaili yang menggambarkan hubungan harmonis antara manusia dengan alam semesta, dengan sesama manusia, dan dengan Tuhan. Tonda Talusi artinya tiga penyangga (tungku) kehidupan masyarakat adat Kaili. Prinsip-prinsip kebersamaan dalam falsafah Tonda Talusi, meliputi 3 pilar kehidupan masyarakat adat Kaili yang dilandasi nilai-nilai kebaikan, yaitu: Matuvu Mosipeili artinya saling melihat, Matuvu Mosiepe artinya saling mendengar, Matuvu Mosimpotove artinya saling mengasihi.